The effect of urinary tract infection on overall mortality in elderly male patients - Caner Baran; Abdullah Talha Akan; Veysel Sezgin; Ahmet Boylu; Çiğdem Arabaci; Emre Can Polat; Alper Ötünçtemur (Folia Medica, 2023)
Introduction: Urinary tract infections are the most common bacterial infections in the older population. Aim: This study aims to determine the impact of the isolated pathogen from urine culture on the estimated survival time of elderly male patients. Materials and methods: We conducted a retrospective cross-sectional study to evaluate the male patients with pathogenic growth in their urine culture tests. We included in the study only male patients aged 80 years or over with positive urine culture tests for pathogenic growth. Urine samples were collected from either first clean-catch midstream urine or from the urinary catheters. Bacterial growth of ≥105 colony-forming units/mL (CFU/mL) in the culture was considered significant. For comparison of the survival time, five groups were created according to the pathogens identified in the urine culture. Results: Between February 2014 and December 2020, there were 1133 patients that met the study criteria. The most common pathogen was Escherichia coli with a rate of 29.5%. The median overall survival time was 4 months. The longest and shortest median overall survival times for the E. coli group and the fungi group were 17.4 months and 0.4 months, respectively (p<0.001). While being in the ICU is the most important risk factor for mortality in this elderly cohort, the statistical analysis showed that being infected with fungi carries a 1.57-fold increased risk of mortality compared with the E. coli infection (p<0.001). Conclusions: The aging of the population requires evaluation of the diseases that are frequently encountered in advanced age. Our study showed that the causative pathogen of the urinary tract infection might have an impact on overall survival time in the senior population.